2016
DOI: 10.1597/14-027
|View full text |Cite
|
Sign up to set email alerts
|

The Americleft Speech Project: A Training and Reliability Study

Abstract: Objective To describe the results of two reliability studies and to assess the effect of training on interrater reliability scores. Design The first study (1) examined interrater and intrarater reliability scores (weighted and unweighted kappas) and (2) compared interrater reliability scores before and after training on the use of the Cleft Audit Protocol for Speech–Augmented (CAPS-A) with British English-speaking children. The second study examined interrater and intrarater reliability on a modified version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
149
0
38

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(192 citation statements)
references
References 96 publications
(172 reference statements)
5
149
0
38
Order By: Relevance
“…Several programs of training have been documented in literature, mostly with positive results. A large number was used in the analysis of vocal aspects, such as roughness and breathiness (14,15,17,18,20) , and only a few in the analysis of nasality (6,7,16,19) . One of the more effective training strategies mentioned in literature is the use of the reference-matching, as the one that used in this study (20) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several programs of training have been documented in literature, mostly with positive results. A large number was used in the analysis of vocal aspects, such as roughness and breathiness (14,15,17,18,20) , and only a few in the analysis of nasality (6,7,16,19) . One of the more effective training strategies mentioned in literature is the use of the reference-matching, as the one that used in this study (20) .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors believe that listeners should be trained prior to the assessment of hypernasality to adjust their internal scales, i.e., they should classify speech samples with different degrees of nasality until they reach an agreement in their own judgments (13) . Studies contemplating the auditory perceptual assessment of voice quality have shown that the use of anchors, prior listener training, and experience of the listeners favor the reliability of results (7,(14)(15)(16)(17)(18)(19) . Regarding the vocal aspects, multiple authors have demonstrated the efficacy in both the listener training and the use of anchors in the perceptual assessment of dysphonia symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variability has been attributed to the types of rating scales used [41] or to listeners’ experience [42, 43]. Studies about listener training have shown improved interrater agreement [44-46]. However, it is largely unknown how listeners perform when there are co-occurring pathologies in more than one perceptual dimension, which is often the case in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos (PAMPLONA et al, 2012;BESSELL et al, 2013) Apesar de existirem métodos objetivos para a avaliação da fala como a avaliação aerodinâmica e análise acústica o julgamento perceptivo-auditivo é o método de avaliação considerado como "padrão ouro" para a caracterização das alterações de fala (GERRATT et al, 1993;KREIMAN et al, 1993;KENT, 1996;KUEHN;MOLLER, 2000;KUMMER et al, 2012;CHAPMAN et al, 2015). A avaliação perceptiva das alterações de fala, incluindo as AC, pode sofrer influência de vários fatores (SANTELMAN; SUSSMAN; CHAPMAN, 1999;GOOCH et al, 2001;HOWARD;HESELWOOD, 2002;HENNINGSSON et al, 2008), dentre estes destacam-se a experiência do avaliador em realizar o julgamento perceptivo-auditivo destas produções (GOOCH et al, 2001;OLSSON, 2004;BRUNNEGARD;LOHMANDER, 2007), bem como a seleção e qualidade das amostras de fala utilizadas durante o julgamento.…”
Section: Revisão De Literaturaunclassified